تقدير تقلبات عوائد العملة المشفرة إثيريوم خلال جائحة كورونا باستخدام نموذج Csgarch - قريسي, ياسين (جامعة الوادي - University of Eloued, 2022)
The aims of This study is to build an econometric model that estimates the volatility that occurs in the cryptomonnaies Ethereum, This is done by studying the return volatility in the Ether and Ethereum Classic series, and understand the way Ethereum works by describing the most important technologies used in Ethereum such as blockchain, smart contracts, mining, tokens, as well as understanding the Ethereum 2.0 system that is based on decentralization, Scalability, and security. The results of This study, that The CSGARCH (1.1) model is the optimized model for estimating the returns of Ethereum, and the GARCH (1.1) model is the optimized model for estimating the returns volatility of Ethereum Classic, It also turns that recent information has a greater impact on volatility.
Estimating the volatility return of Cryptomonnaies Ethereum during the Corona pandemic using CSGARCH models
مقال
Keywords: الاثيريوم ; العملات المشفرة ; سلسلة الكتل ; نموذج CSGARCH ; جائحة كورونا